2019
DOI: 10.1002/cctc.201900739
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight‐Driven Production of Methylcyclohexane from Water and Toluene Using ZnSe : Cu(In,Ga)Se2‐Based Photocathode

Abstract: A three‐dimensional reaction field composed of a thick, porous TiO2 layer decorated with Pt and an anionic ionomer was fabricated on the surface of a membrane photocathode assembly (MPA). This MPA comprised (ZnSe)0.85(CuIn0.7Ga0.3Se2)0.15 (ZnSe : CIGS) particles that promoted the photoelectrochemical (PEC) production of methylcyclohexane (MCH) from toluene and water. The Pt/TiO2 layer provided selective active sites for MCH production as well as reactant supply pathways. A tandem PEC cell consisting of the Pt/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The transparency of the TiO 2 in the visible light region should ensure the light transmission to the ZnSe : CIGS particles even when using such a thick layer. The EDS line analyses of the surface of the Pt/TiO 2 ‐modifed (1500 rpm) photocathode revealed that the distribution of Pt well agreed with that of Ti and O as shown in Figure e, supporting the fact that Pt was highly uniformly dispersed over the whole TiO 2 layer . In the previous report, the high‐resolution transmission electron microscopy (HRTEM) and the scanning transmission electron microscopy (STEM) observations have also revealed that 2–6 nm of crystalline Pt particles were highly dispersed throughout the TiO 2 layer .…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…The transparency of the TiO 2 in the visible light region should ensure the light transmission to the ZnSe : CIGS particles even when using such a thick layer. The EDS line analyses of the surface of the Pt/TiO 2 ‐modifed (1500 rpm) photocathode revealed that the distribution of Pt well agreed with that of Ti and O as shown in Figure e, supporting the fact that Pt was highly uniformly dispersed over the whole TiO 2 layer . In the previous report, the high‐resolution transmission electron microscopy (HRTEM) and the scanning transmission electron microscopy (STEM) observations have also revealed that 2–6 nm of crystalline Pt particles were highly dispersed throughout the TiO 2 layer .…”
Section: Resultssupporting
confidence: 74%
“…Figure shows the scanning electron microscopy (SEM) images for the ZnSe : CIGS particles and the Pt/TiO 2 ‐modified photocathodes. The ZnSe : CIGS photocathodes were fabricated by the particle transfer (PT) method and modified with various thicknesses of the Pt/TiO 2 layer by spin coating at different rotating speeds. ZnSe : CIGS particles synthesized via the flux method were comprised of triangular‐shaped crystals with a relatively wide particle size range from submicron to several micron‐order (see Figure a), similar to that in a previous report .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations